RiboD: A comprehensive database for prokaryotic riboswitches - Mukherjee S.; Das Mandal S.; Gupta N.; Drory-Retwitzer M.; Barash D.; Sengupta S. (My University, 2025)
Riboswitches are cis-regulatory non-coding genomic segments that control the expression of downstream genes by undergoing conformational change upon ligand binding. We present a comprehensive database of prokaryotic riboswitches that allows the user to search for riboswitches using multiple criteria, extract information about riboswitch location and gene/operon it regulates. RiboD provides a very useful resource that can be utilized for the better understanding of riboswitch-based gene regulation in bacteria and archaea. Availability and implementation: RiboD can be freely accessed on the web at http://ribod.iiserkol.ac.in/. © 2019 The Author(s) 2019. Published by Oxford University Press. All rights reserved.